Intragastric botulinum toxin injection for weight loss: current trends, shortcomings and future perspective - Erfan Arabpour; Hadi Golmoradi; Parya Mozafari Komesh Tape; Amir Sadeghi; Mohammad Abdehagh; Pardis Ketabi Moghadam; Mohammad Reza Zali (Clinical Endoscopy)
The administration of botulinum toxin A (BTA) into the gastric wall has emerged as a novel endoscopic bariatric procedure. Although over 20 years have elapsed since the initial human trial of intragastric BTA injection, considerable debate remains surrounding the safety, efficacy, and procedural instructions of this approach. The current literature exhibits discrepancies in the methodologies employed across studies, including differences in the dosage of BTA administered, injection site, number and depth of injections, post-procedural dietary modifications, and follow-up duration. This study reviewed the state-of-the-art use of BTA for weight loss and focused on the clinical evidence of the therapeutic applications of BTA for obesity. Studies with consistent outcome measures and methodologies are necessary to thoroughly assess the potential effects of BTA on weight management.